Lightweight Block Cipher for Security in Resource-Constrained Network - Gupta, Aruna; Sasikala, T. (International Journal of Electrical and Computer Engineering Systems, 2025)
As the proliferation of resource-constrained devices continues in various application domains, the need for energy-efficient cryptographic algorithms becomes paramount for ensuring their security. Lightweight block ciphers play a crucial role in securing communication and data integrity in resource-poor environments. This paper presents the design, simulation, and evaluation of a novel symmetric Energy Efficient Lightweight Block Cipher (EE-LBC), tailored for such environments, which employs a balanced combination of substitution-permutation network (SPN) structure with larger diffusion and substitution box activation properties to achieve high security with minimal energy consumption and implementation cost. Through rigorous cryptanalysis and performance evaluations, EE-LBC demonstrates superior throughput and efficiency compared to prevailing lightweight block ciphers, making it an ideal choice for securing resource-constrained network.